Feeding cashew trees the high-tech way - Rupa, T R; Pandey, V (Indian Horticulture, 2019)
Cashew (Anacardium occidentale) is the most important horticultural crop grown in India. India occupies the largest area under cashew. Its share in area and production is 20 and 16 per cent, respectively. Major cashew-growing states are Maharashtra, Goa, Karnataka and Kerala along the west coast and Tamil Nadu, Andhra Pradesh, Odisha and West Bengal. In India, its productivity level is not increasing at the expected rate over the last few years. Growing cashew in degraded lands and lack of proper nutrient management are some of the major reasons for low productivity. Exploitation of production potential of high-yielding varieties through better nutrient management is one of the strategies for enhancing cashew productivity.